2020
DOI: 10.21037/tcr-20-2172
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in COVID-19 patient affected by multiple myeloma: a case report

Abstract: In COVID-19 pandemic, cancer patients may be vulnerable for their immunological status and need of immunosuppressive anti-neoplastic treatments. Choosing the best treatment option in COVID-19 positive cancer patients is still a challenging issue. We report the case of a 62-year-old woman diagnosed with multiple myeloma and affected by COVID-19. After the diagnosis of multiple myeloma in January 2019, the patient underwent first line therapy followed by bone marrow autologous stem cell transplantation, achievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…For example, Krengli et al 24 reported that radiation therapy could be considered a treatment strategy in COVID‐19 patients affected by myeloma. Recently, Liu et al 25 demonstrated that patients with hematological malignancies were at a higher risk of death if they received chemotherapy 3 months before the COVID‐19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Krengli et al 24 reported that radiation therapy could be considered a treatment strategy in COVID‐19 patients affected by myeloma. Recently, Liu et al 25 demonstrated that patients with hematological malignancies were at a higher risk of death if they received chemotherapy 3 months before the COVID‐19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been demonstrated that radiation therapy has no higher risk of severe events related to the COVID-19 for these patients. 5 For example, Krengli et al 24 with hematological malignancies were at a higher risk of death if they received chemotherapy 3 months before the COVID-19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This left 57 full-text articles to be assessed for eligibility. Thirty-six of these studies met our eligibility criteria [ 16 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These studies included a total of 2011 patients, 516 of whom underwent SCT.…”
Section: Resultsmentioning
confidence: 99%
“… Pooled event rate for COVID-19–related mortality [ 16 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 , 50 , 52 , 53 , 54 , 56 , 58 , 60 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation